TAFSIR EKSTREM KAUM KHAWARIJ KETIKA AYAT SUCI DIJADIKAN ALAT TAKFIR - Akhmad Dasuki; Muhammad Samman; Helda Pauziah; Monica Putri; Zesar Rahmat Syafe’i (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the exegetical methodology and interpretive patterns of the Khawarij, a sect that emerged from political and theological conflicts following the arbitration between Ali ibn Abi Talib and Mu’awiyah ibn Abi Sufyan. The background of this research lies in the need to understand how early extremist groups such as the Khawarij interpreted the Qur’an in a literal and textual manner, and how these interpretations impacted religious and socio-political practices. This research employs a qualitative descriptive approach using library research methods, gathering data from classical tafsir works, Islamic historical literature, and contemporary academic journals discussing the Khawarij. The study compares Khawarij exegesis with the mainstream Sunni tradition, which emphasizes contextual and inclusive interpretations. The findings reveal that Khawarij interpretation falls into three main categories: fiqhi (legal), ideological, and socio-political, all rooted in a rigid understanding of Qur’anic texts without considering the asbab al-nuzul (occasions of revelation) or maqasid al-shariah (objectives of Islamic law). Among Khawarij factions, Ibadhiyah represents the most moderate strand and still exists today. The study concludes that although Khawarij interpretation holds historical significance, it has had limited influence on contemporary Qur’anic studies due to its rigid and exclusionary hermeneutical framework.